Pengaruh Medsos Terhadap Kesejahteraan Emosional Remaja - Difa Nur Novila Ramadhanti; Khabibah Twoizah; Heny Susilowati; Iskandar Dzulkarnain; Denny Otavina Radianto (Jurnal Multidisiplin Dehasen (MUDE), 2023)
The influence of social media (medsos) on the emotional well-being of adolescents has become a topic of increasing importance in recent years. Social media, such as Facebook, Instagram, Twitter and Snapchat, have changed the way teenagers interact and communicate with other people. However, the impact that the use of social media has on the emotional well-being of adolescents has a complex side. One of the main influences of social media on adolescents' emotional well-being is feelings of dissatisfaction with themselves and social comparison. In a virtual world that is often filled with the best photos and seemingly perfect lives, it's easy for teenagers to get caught up in feelings of inferiority and anxiety over the judgment of others. They often compare their life to the ideal life presented on social media, and this can lead to depression, anxiety and other emotional well-being issues. In addition, excessive use of social media can also trigger feelings of alienation and loneliness in adolescents. While they can connect with many people through these platforms, these virtual interactions often don't have the same depth as in real life. Teenagers may feel less emotionally and socially connected, as they focus more on interacting through screens than on developing direct relationships with others. This can lead to feelings of loneliness and loss of social connections that are important for their emotional development. In addition, bullying and online bullying (cyberbullying) are also one of the negative impacts of using social media on the emotional well-being of adolescents. Teenagers are often the target of verbal abuse, threats or defamation through social media platforms. This can seriously impact a teenager's mental and emotional health, increasing the risk of depression, anxiety, and even suicidal ideation. However, it is also important to remember that social media can also have a positive influence on adolescents' emotional well-being. They can help teens make new social connections, express themselves, and seek support from similar online communities. Apart from that, social media can also be a valuable source of information and knowledge for teenagers, if used wisely and with discipline.